How Might Changes in Legislation Impact the Development of Entrepreneurship? - Mojca Kunsek; Danila Djokic (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
In the Action Plan for Entrepreneurship 2020, the fundamental purpose of the European Commission is to revive the entrepreneurial spirit in Europe after the economic crisis from the past years. At the same time, the European Commission strives to take an action in various areas of approach and implementation of entrepreneurial activity as the main lever for the growth of economic development and raising the level of employment. In recent years, the Slovenian turbulent economy has caused different ways of the entrepreneurship development. Beside the wellknown hypothesis that #of newly established companies shows the entrepreneurship development and their influence to the national GDP, the results of slovene promotors of entrepreneurship and specially the Global Entrepreneurship Monitor (GEM) shows different results which can serve as a basis for the adoption appropriate government policies for future entrepreneurship development and economic growth. Slovenia moved from a socialist economy to a trade economy, with its independence in 1991. The First Companies Act (ZGD) was adopted in 1993 and laid down the foundations for entrepreneurial behavior. This was followed by other bases, such as the Enterprise Supporting Environment Act, aiming to increase the chances of setting up new businesses and creating new jobs and to establish an effective support system for entrepreneurs at all stages of their development. Pursuant to the Act on the Court Register and the Business Register of Slovenia Act, Slovenia offers free and easy entry to entrepreneurship through the one stop shop points system (VEM), where the prospective entrepreneur can register his / her business. For the VEM system, which has been operating since 2005, the Republic of Slovenia received the 2009 United Nations Public Service Award. According the Slovenian Enterprise Fund and other national providers of registering and assistance in starting up entrepreneurship, the most common mistakes of failed start-ups are excessive entrepreneurial optimism and unrealistic entrepreneurial plan, lack of entrepreneurial knowledge, poor knowledge of regulations and financial obligations and lack of capital which were expected. However according to the results of GEM Slovenia 2015, among the reasons for the termination of entrepreneurs' business, far more than in other EU economies, reflection of the company's unreliability and financial options are recognised, and less than in other EU economies, reflection of Creating qualitative entrepreneurial ecosystem is a mix of different government / tax policies. factors, which consists of government policies and programs for entrepreneurship, education and training, access to business and professional infrastructure, and also cultural and social norms. According to the results of the GEM 2015, despite expected lack of entrepreneurship financing, Slovenia surprisingly is under the European average at the level of entrepreneurial education and the social acceptance of entrepreneurship. On the basis of the cultural and sociological background of this challenge, however, the foundations of a different behavior and a greater acceptance of entrepreneurship will undoubtedly be conditioned by appropriate legal bases and promotional activities, where have already been seen certain activities for more positive attitude towards qualitative entrepreneurship.
Keywords: 650; Legislation; Entrepreneurship; Governance; Ecosystem